The Frequency Response of the Vibrissae of Harp Seal, Pagophilus Groenlandicus, to Sound in Air and Water - Shatz, Lisa F. (Public Library of Science, 2013)
The motion of isolated seal vibrissae due to low frequency sound in air has been measured using a microscope with a video camera and modeled using an FEM method with good agreement between the measurements and the model; the model has also been used to predict the motion of seal vibrissae in water. The shape of the seal vibrissae is that of a tapered right rectangular prism, unlike that of the previously studied rat vibrissae which are conical in shape. Moreover, unlike rat vibrissae which oscillate in the direction of the sound stimulus, two different modes of vibration of seal vibrissae were observed – one corresponding to the wider side being stimulated and one with the narrow side stimulated. The tuning of the seal vibrissae was much sharper than those of rat vibrissae, with quality factors about three times as large as those of rat vibrissae. As shown by the model, this increased sharpness is caused by the larger cross-sectional areas (by more than a factor of ten) of the seal vibrissae. This increased sharpness may be necessary for seal vibrissae so that they can have tuning in water, where the drag more heavily dampens the tuning than in air. The results suggest that vibrissae tuning may be important in the seal's ability to track the wake of its prey.